Thermal performance of ferrule designs for medium voltage cable jointing - Miswan, Normi Salwana; Abd Halim, Huzainie Shafi; Hizam, Hashim (IEEE, 2009)
Among breakdowns reported in Tenaga Nasional Berhad (TNB) Malaysia is about 60% of total breakdown is due to underground network failures. It was known that cable joint is the weakest part in the underground cable system and ferrule is one part of cable joint. The main reason of ferrule failure is due to excessive heat generated at the connection between conductor and ferrule. There are many ferrules available in the market. This study will focus on two types of ferrule and the experiment was setup to evaluate the thermal performance.